Platelet distribution width correlates with prognosis of non-small cell lung cancer - Ming-ming Cui (Nature Portfolio, 2017)
Abstract Platelets play a multifaceted role in cancer progression and metastasis. Mean platelet volume (MPV) and platelet distribution width (PDW) are commonly used platelet parameters from routine blood test. The aim of the present study was to investigate the correlation between platelet indices and prognosis in patients with non-small cell lung cancer (NSCLC). A total of 270 patients who were diagnosed with NSCLC between January 2009 and December 2009 were retrospectively analyzed. Patients’ characteristics and hematologic tests data at initial diagnosis were collected. The overall survival rate was estimated using Kaplan-Meier method. The prognostic analysis was carried out with univariate and multivariate Cox regressions model. Reduced PDW was significantly correlated with T stage, N stage, TNM stage, and histological type of the disease. Moreover, survival analysis showed that the overall survival of patients with PDW ≥ 16.3% was significantly longer than that of those with PDW < 16.3% (P < 0.001). In multivariate Cox regression model, age, sex, TNM stage, and PDW were identified as independent prognostic factors for overall survival (for PDW, P < 0.001). In conclusion, reduced PDW is an unfavorable predictive factor of NSCLC patient survival. Further studies are warranted.